BITWARDEN: YOUR KEY TO SECURE PASSWORD MANAGEMENT - Kodirov , Akhmadkhon Avazkhon ugli (Educational Research in Universal Sciences, 2023)
Bitwarden is an open-source password manager that excels in providing robust security and user-friendly features. This article explores Bitwarden’s significance in the realm of password management, its open-source nature, security measures, and its applications. It also addresses the ethical and safety considerations surrounding the use of such tools.